PENGARUH INHALASI AROMATERAPI LAVENDER TERHADAP TINGKAT KECEMASAN IBU NIFAS DI RUMAH SAKIT UMUM DAERAH BALI MANDARA PROVINSI BALI - Sapitri, Ni Wayan Ari; Rahyani, Ni Komang Yuni; Somoyani, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p32, 2025)
ABSTRACT Postpartum women anxiety causes psychological disorders that can reduce contact with their babies. Lavender aromatherapy is believed to reduce anxiety levels. The purpose of this study was to determine the effect of lavender aromatherapy inhalation on the anxiety level of postpartum women. This research is a pre-experimental study with a one-group pretest-posttest design. Implementation in March–April 2023. A sample of 17 postpartum women was taken using a purposive sampling technique. Lavender aromatherapy inhalation is done by dripping five drops of lavender essential oil into a diffuser containing 30 cc of distilled water for 15 minutes on three consecutive days. Before and after giving aromatherapy, respondents will fill out the HRS-A questionnaire. Data analysis was univariate in the form of a frequency distribution, and bivariate analysis used the Wilcoxon test. Wilcoxon test showed a significant difference before and after being given lavender aromatherapy inhalation, which means that there is an effect of lavender aromatherapy inhalation on the anxiety level of postpartum women. Postpartum women are expected to be able to use lavender aromatherapy inhalation as a non-pharmacological therapy to overcome anxiety during the postpartum period. Keywords:  lavender aromatherapy, anxiety level, postpartum women